The private construction industry: its participation in Moquegua's PBI, 2013-2017 - Vilcanqui Chambi, Brady Manuel (2020)
This research aimed to determine the incidence of private investments in the construction sector as the capital investment, the construction licenses processed and skilled labor in Moquegua's Gross Domestic Product from 2013 to 2017. The method used this research is basic and explanatory non experimental with a retrospective study design applying document analysis and using available information from public institutions, whose results were statistically analyzed through linear regression. It is concluded that private investment in the construction sector has directly incidence in Moquegua's Gross Domestic Product from 2013 to 2017, with a growing, positive, and constant tendency.